When Parents Decide: Gender Differences in Competitiveness - Jonas Tungodden; Alexander Willén (Center for Economic Studies and ifo Institute (CESifo), 2022)
Parents make important choices for their children in many areas of life, yet the empirical literature on this topic is scarce. We study parents' competitiveness choices for their children by combining two large-scale artefactual field experiments with high-quality longitudinal administrative data. We document three main sets of findings. First, parents choose more competition for their sons than daughters. Second, this gender difference can largely be explained by parents' beliefs about their children's competitiveness preferences. Third, parents' choices predict children's later-in-life educational outcomes. Taken together, these findings provide novel evidence on the role of parents in shaping children's long-term outcomes.
Keywords: 330